Determinants of the use of family planning methods among rural women in Plateau state, Nigeria - Shemu, Piritmwa L.; Ahmad, Norliza; Poh, Ying Lim; Suchi, Plangshak M. (Women's Health and Action Research Centre (WHARC), 2022)
This study aimed at determining the factors that influence family planning practice among rural women of Pankshin district in Plateau state, Nigeria. A cross-sectional study using a simple random sampling method was conducted from October to December 2019. A self-administered questionnaire was used for data collection among 302 respondents. Among respondents, 48.3% had practised family planning and the most popular family planning method ever practised was injectables (57.5%). The determinants of family planning practice were age group 29-39 and 40-49 years old (AOR=4.373, p<0.001; AOR=5.862, p<0.001), discussion with partner (AOR=9.192, p<0.001) and partner’s approval (AOR=2.791, p=0.007). Findings showed an encouraging family planning prevalence with the main determinants involving male partners. Further efforts need to be made to promote family planning practice among male partners and to empower women of all reproductive age groups by providing them with relevant information that is needed for them to make informed decisions.